2004
DOI: 10.1021/la036349s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Polydispersity of Polymeric Surfactants on the Enantioselectivity of Chiral Compounds in Micellar Electrokinetic Chromatography

Abstract: Poly(sodium undecenoyl-L-leucinate) (poly-L-SUL) was fractionated by the use of different molecular weight cutoff (MWCO) filters to narrow the polydispersity of the macromolecular sizes of the polymeric surfactant. The resulting polymeric surfactant fractions were characterized by the use of three techniques: (1) pulsed field gradient nuclear magnetic resonance (PFG-NMR) was used to determine the hydrodynamic radii, (2) analytical ultracentrifugation (AUC) was used to determine the molecular weights, and (3) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…The effects of molecular weight and polydispersity of polySUL on various properties and EKC separation of PTH-amino acids and coumarinic derivatives were studied by first fractionating a synthesis of poly(SUL) into three molecular weight fractions (5-10 k, 10-30 k, and .30 k) using centrifugal dialysis membrane filters [42]. Unfractionated poly(SUL) was polydispersed and was distributed among the various fractions with the majority of the material in the high molecular weight fraction.…”
Section: Chiral Polymers and Separationsmentioning
confidence: 99%
“…The effects of molecular weight and polydispersity of polySUL on various properties and EKC separation of PTH-amino acids and coumarinic derivatives were studied by first fractionating a synthesis of poly(SUL) into three molecular weight fractions (5-10 k, 10-30 k, and .30 k) using centrifugal dialysis membrane filters [42]. Unfractionated poly(SUL) was polydispersed and was distributed among the various fractions with the majority of the material in the high molecular weight fraction.…”
Section: Chiral Polymers and Separationsmentioning
confidence: 99%
“…1c) are a further variation on MEKC. Since 2003, the literature regarding polymer micelles has focused on their characterization [38][39][40][41][42][43][44] and applicability [4,36,43,[45][46][47][48][49][50][51]. Polymer micelles have notably different characteristics than conventional micelles.…”
Section: Surfactants and Additivesmentioning
confidence: 99%
“…Actually, Tarus et al reported that the polymerization degree of poly(sodium undecanoyl-L-leucinate) strongly affected the efficiency and resolution of racemic amino acid derivatives. 6 Thus, the introduction of mono-dispersed micelles with no or lower CMC is still desired in MEKC.…”
Section: Introductionmentioning
confidence: 99%